Impact of Body Mass Index on Outcomes in Cardiac Surgery. Issue 1 (February 2017) - Gao, M.; Sun, J.; Young, N.; Boyd, D.; Atkins, Z.; Li, Z.; Ding, Q.; Diehl, J.; Liu, H.
Abstract : (Abstracted from J Cardiothorac Vasc Anesth, 30(5):1308–1316, 2016) Body mass index (BMI) is defined as weight in kilograms divided by height in meters and is used in classifying obesity; a person with BMI of greater than 30 kg/m 2 is defined as obese, and a person with BMI equal to 25 to 29.9 kg/m 2 is defined as overweight. Obesity has been observed to be associated with several risk factors for cardiovascular disease, which include hypertension, dyslipidemia, insulin resistance, and diabetes mellitus.